Jurisprudence Differences between the Single Agency and Implicit in Companies in the Hanafi School: Doctrinal study through the book Deeds of Al-Kasani - Abu Jaber, Mamoun Mujalli (Dirasat: Shari'a and Law Sciences, 2021)
The research deals with juristic differences between the single agency and the agency related to companies according to Hanafi School. It also sets definition of the implicit agency, jurisprudence rules and controls that affected the formation of these differences. It appears that they include sixteen differences, two rules, and two controls. The study followed the inductive method to extrapolate the differences that came in the innovations in the book of companies, text and reference, with documentation from the books of the doctrine and the analytical method to analyze the doctrinal differences between the two agencies through the phrase al-Kasani, to find the rules and controls that influenced the differences and the deductive method, where the researcher worked to extract the rules and controls that influenced the formation of these differences, and employ them to serve the research. The research showed how the juristic differences between the two agencies formed one of the reasons for the difference between the jurists, the fact that companies at the Hanafi school are on the basis of "what the authorization is permitted for, the company is permissible in," and the effect of the difference between the Hanafi imams in the size of the jurisprudence differences. The researcher recommends the need to pay attention to studies related to the juristic differences in the section of transactions from the Shariah point of view, and compare them with Legal Studies in the field of wakala and individual and implicit guarantee.